Applicability of Mixolab test with local wheat flours - Daniel Vazquez; Marıa C. Veira (International Journal of Food Studies)
Several types of equipment have been used to predict dough behaviour during breadmaking. The complexity of requirements means that no device is able to predict all the properties, and therefore, new tests are released continuously. The Chopin Mixolab mixes the dough at different temperatures, allowing the study of dough mixing properties, weakening, gelatinization, gel stability and retrogradation in one test. The objective of this work was to study the suitability of the Mixolab to predict rheological properties and breadmaking quality of local wheats. Flour was obtained from 29 wheat samples from different genotypes and environments. The correlation of results from traditional analyses (test weight, protein content, sedimentation volume, wet gluten, Falling Number, Alveograph and Farinograph) with Mixolab parameters was studied. The properties of two different bread types were compared with all these parameters. Stability and water absorption values from the Farinograph were highly correlated with the respective Mixolab parameters. It was concluded that wheat samples could be sorted by mixing properties in similar order independently of which method was used. Beyond that, gluten strength estimators obtained from these three rheological methods and the sedimentation volume test were highly correlated. Whilst the correlation of Mixolab parameters with pan loaf volume was not as high as traditional ones, Mixolab developing time, stability and C5 were the best correlated with the most important hearth bread characteristics. Studies performed by other researchers, using wheats from diverse origins, found different results. The need for empirical rheology evaluation with local wheat samples was proved.